The effectiveness of argumentation based learning and problem based learning models in improving student’s argumentation skills about salt hydrolysis concept - Anisa Puspita Sari; Harizon Harizon; Muhammad Haris Effendi-Hasibuan (Pascasarjana Universitas Negeri Medan, 2021)
Learning model that can train students in developing their argumentative skills includes the Argumentation Based Learning (ABL) and Problem Based Learning (PBL). This study aimed to see the effectiveness of the ABL and PBL models in improving students' argumentation skills about the concept of salt hydrolysis. The study was conducted in the class XI MIA SMAN 1 Tebo Jambi with a sample consisting of two classes. Some 50 students were recruited purposively to be the participants of this study. Concurrent embedded mix method using two group pretest posttest control group design was used in this study. The results of independent t-test showed that ABL was more effective than PBL (t= 4.864; p-value=0.00 < 0.05) in improving the students' argumentation skills. This was supported by the N-gain test of ABL which was 0.82 and the N -Gain test of PBL was 0.68. The results of observations revealed that the ABL students had more intensive opportunities to debate their argumentation than those in the PBL class. This was believed as the major factor influencing the difference in the students’ argumentation skills. Keywords: argumentation based learning, argumentation skill, problem based learning, salt hydrolysis